1994
DOI: 10.1093/jnci/86.8.589
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and Serum Organochlorines: a Prospective Study Among White, Black, and Asian Women

Abstract: Future investigations must consider the biologic mechanisms involved and variations in exposure to chemical pollutants and of breast cancer incidence rates among diverse groups of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
215
3
8

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 431 publications
(243 citation statements)
references
References 0 publications
15
215
3
8
Order By: Relevance
“…It is possible that the serum organochlorine levels measured in the study population are too low to influence breast cancer risk. Our levels of PCBs and DDE, as well as those of African American women in North Carolina collected during the 1990s (16), are substantially lower than those reported by Krieger et al (22), which were measured in the 1960s. However, compared to those measured in Caucasian women from samples taken in the 1990s, our levels and those measured among North Carolina black women are approximately 1.0 and 0.15 μg/g higher for lipidadjusted DDE and PCBs, respectively (16).…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…It is possible that the serum organochlorine levels measured in the study population are too low to influence breast cancer risk. Our levels of PCBs and DDE, as well as those of African American women in North Carolina collected during the 1990s (16), are substantially lower than those reported by Krieger et al (22), which were measured in the 1960s. However, compared to those measured in Caucasian women from samples taken in the 1990s, our levels and those measured among North Carolina black women are approximately 1.0 and 0.15 μg/g higher for lipidadjusted DDE and PCBs, respectively (16).…”
Section: Discussioncontrasting
confidence: 74%
“…The majority of the earliest case-control studies were null but these also tended to have small sample sizes, did not study a well-defined population or failed to control for breast cancer risk factors that could have confounded the comparison between case patients and controls (10-13). Recent larger case-control studies that more carefully controlled for confounding factors have provided mixed results with some positive findings among subgroups of the populations defined by tumor receptor status but with limited statistical power to evaluate subgroups (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Among the positive studies, one (28) reported a significant difference in DDE between breast cancer case patients and controls, as well as an almost 4-fold increase in risk comparing the highest quintile of DDE to the lowest; however, the values for serum organochlorine levels were not lipid adjusted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations